Structure-based developmental toxicity and ASD-phenotypes of bisphenol A analogues in embryonic zebrafish - Chenglian Bai; Yi Zheng; Linjie Tian; Jian Lin; Yang Song; Changjiang Huang; Qiaoxiang Dong; Jiangfei Chen (Ecotoxicology and Environmental Safety, 2023)
Autism spectrum disorder (ASD) is a neurodevelopmental disorder that has become more prevalent in recent years. Environmental endocrine disruptor bisphenol A (BPA) has been linked to ASD. BPA analogues (BPs) are structure-modified substitutes widely used as safer alternatives in consumer products, yet few studies have explored the developmental neurotoxicity (DNT) of BPA analogues. In the present study, we used the larval zebrafish model to assess the DNT effects of BPA and its analogues. Our results showed that many BPA analogues are more toxic than BPA in the embryonic zebrafish assay regarding teratogenic effect and mortality, which may partially due to differences in lipophilicity and/or different substitutes of structural function groups such as CF3, benzene, or cyclohexane. At sublethal concentrations, zebrafish embryos exposed to BPA or BPs also displayed reduced prosocial behavior in later larval development, evidenced by increased nearest neighbor distance (NND) and the interindividual distance (IID) in shoaling, which appears to be structurally independent. An in-depth analysis of BPA, bisphenol F (BPF), and bisphenol S (BPS) revealed macrocephaly and ASD-like behavioral deficits resulting from exposures to sublethal concentrations of these chemicals. The ASD-like behavioral deficits were characterized by hyperactivity, increased anxiety-like behavior, and decreased social contact. Mechanistically, accelerated neurogenesis that manifested by increased cell proliferation, the proportion of newborn mature neurons, and the number of neural stem cells in proliferation, as well as upregulated genes related to the K+ channels, may have contributed to the observed ASD-like morphological and behavioral alterations. Our findings indicate that BPF and BPS may also pose significant risks to ASD development in humans and highlight the importance of a comprehensive assessment of DNT effects for all BPA analogues in the future.